Behaviour of reinforced concrete deep beams under fatigue loading - Ma, Wei (2009)
In this project, a total of 24 reinforced concrete deep beams with shear span to depth ratios (a/h) of 1.0 and 1.5 were tested. Different arrangements of web reinforcements, i.e. without web reinforcement, with vertical web reinforcement, with orthogonal web reinforcements, and with inclined web reinforcement, were also investigated. The tests reveal that web reinforcement and repeated load range has significant influences on the structural responses of deep beams. The tests also show that with load repetitions, the midspan deflections and the maximum crack-widths increase, while shear strengths decrease.